2018
DOI: 10.3390/sports6020047
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Physical Performance of Youth Handball Players: The Role of the Relative Age

Abstract: Background: The relative age effect is essential throughout all of the talent selection processes in sports, especially during adolescence, which leaves fewer athletes within each cohort that are born late in the selected year. The aim of the present study was to examine the role of relative age in anthropometric and physical performance characteristics of youth handball players by gender. Methods: The sample that was selected included 47 participants (male n = 23, female n = 24). The data collection included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 46 publications
5
39
0
12
Order By: Relevance
“…Interestingly, we reported similar upper limb strength in our U18 category to that reported by Vila Suárez et al [17] in Spanish handball youths from the same category. With respect to lower limb strength, our CMJ and SJ values were similar to the those reported by Ingebrigtsen et al [16] in both the U16 and U18 categories, and the ABK value in U14 athletes reported by Camacho-Cardenosa et al [10]. As for cardiorespiratory capacity, the values obtained by Camacho-Cardenosa et al [10] and Rousanoglou et al [12] were higher in the three analyzed categories.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Interestingly, we reported similar upper limb strength in our U18 category to that reported by Vila Suárez et al [17] in Spanish handball youths from the same category. With respect to lower limb strength, our CMJ and SJ values were similar to the those reported by Ingebrigtsen et al [16] in both the U16 and U18 categories, and the ABK value in U14 athletes reported by Camacho-Cardenosa et al [10]. As for cardiorespiratory capacity, the values obtained by Camacho-Cardenosa et al [10] and Rousanoglou et al [12] were higher in the three analyzed categories.…”
Section: Discussionsupporting
confidence: 90%
“…With respect to lower limb strength, our CMJ and SJ values were similar to the those reported by Ingebrigtsen et al [16] in both the U16 and U18 categories, and the ABK value in U14 athletes reported by Camacho-Cardenosa et al [10]. As for cardiorespiratory capacity, the values obtained by Camacho-Cardenosa et al [10] and Rousanoglou et al [12] were higher in the three analyzed categories. Surprisingly, we observed clear differences for VO 2 max comparison, especially in our U18 category, although the last study mentioned used the 20-m shuttle run test without considering the intermittent activity that handball presents, so its values may have been overestimated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the actions performed by athletes in different playing positions require distinct skill demands [10,11,12]. Thus, physical (e.g., strength, speed, and endurance), cognitive (e.g., decision-making performance), and anthropometric attributes (e.g., height) are individual constraints used by coaches to select and define playing positions [13]. In fact, evidence shows such characteristics favor the occurrence of RAE in handball, and playing position act as a constraint to the phenomenon [8,14].…”
Section: Introductionmentioning
confidence: 99%